Association between genotoxic properties of inhalation anesthetics and oxidative stress biomarkers. (June 2020) - Neghab, Masoud; Kargar-Shouroki, Fatemeh; Mozdarani, Hossein; Yousefinejad, Saeed; Alipour, Hamzeh; Fardid, Reza
Exposure to inhalation anesthetics (IAs) has been associated with DNA damage as reflected in the increased frequency of micronuclei (MN) and chromosomal aberrations (CAs). The present study was undertaken to ascertain whether there was any correlation between increased MN and CA and the extent of oxidative stress as well as the antioxidant status of a group of operating room personnel exposed to a mixture of IAs, including nitrous oxide, isoflurane, and sevoflurane. In this cross-sectional study, 60 operating room personnel (exposed group) in whom the frequencies of MN and CA had already been shown to be significantly higher than those of a referent group, as well as 60 unexposed nurses, were studied. Venous blood samples were taken from all participants, and malondialdehyde (MDA) levels as an index of oxidative stress (OS) and the activity of superoxide dismutase (SOD) and levels of total antioxidant capacity (TAC) as indices of antioxidant status were measured. The level of TAC (1.76 ± 0.59 mM vs. 2.13 ± 0.64 mM, p = 0.001) and the activity of SOD (11.22 ± 5.11 U/ml vs. 13.36 ± 4.12 U/ml, p = 0.01) were significantly lower, while the mean value of MDA was significantly higher (2.46 ± 0.66 µM vs. 2.19 ± 0.68 µM, p = 0.03) in the exposed group than in the nonexposed group. After adjusting for potential confounders, there were statistically significant associations between exposure to IAs, gender, SOD, and TAC with MN frequency and between exposure to IAs and SOD with numbers of CA. The findings of the present study indicated that exposure to IAs was associated with OS, and this, in turn, may be causally linked with DNA damage.